Optimizing stock returns: exploring the effects of profitability, leverage, and dividend policy on inflatio moderation – in-depth study of LQ45 companies - Kamesywara, Saskia Farrasdita; Malini, Helma; Pebrianti, Wenny; Mufrihah, Mazayatul; Mustarudin, Mustarudin (Enrichment : Journal of Management, 2023)
Investors primarily rely on the stock’s return as the primary indicator to evaluate the profitability of their investment in a company and how the company's performance affects the value of their investment over time. Investors conduct fundamental analysis and look at macroeconomic factors to obtain high returns before investing in a particular company. The aim of this research is to investigate how profitability, dividend policy, and leverage influence stock returns, and to assess how inflation may moderate this relationship. This study's population consists of twenty corporations listed on the LQ45 stock market index in Indonesia between 2018 and 2022. Multiple linear regression analysis is utilized, with inflation as the moderating variable. The study also includes a literature review on agency theory and the importance of investors obtaining comprehensive information about potential returns and risks before investing in a company. The study's findings can provide valuable insights for investors in analyzing these factors before allocating their investments. They also guide for companies to improve their standards and send positive signals to investors